Entrepreneurial intentions among MBA students - Kwaku Amofah; Ramon Saladrigues; Ellis Kofi Akwaa-Sekyi (Cogent Business & Management, 2020)
Increasing entrepreneurial activities in a country start with an intention that leads to increased innovative activities, wealth creation, industrialization, employment generation, economic growth, and development. This paper examines the effect of attitude towards entrepreneurship, subjective norm, locus of control, entrepreneurial self-efficacy, and environmental support on entrepreneurial intention of 159 MBA students from two private universities in Ghana. The study uses structural equation modelling (SEM) to analyze the data obtained from the participants. The results show that all the factors but entrepreneurial self-efficacy significantly affects students' entrepreneurial intentions. The study proffers policy-makers with the opportunity to nurture entrepreneurship in students as a foundation for transforming the intent into practice to address the huge employment gaps in emerging economies.
Keywords: 650; entrepreneurial intentions; students; theory of planned behaviour